2010
DOI: 10.1152/ajpheart.00120.2010
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of epicardial and subcutaneous adipose tissue reveals differences in proteins involved in oxidative stress

Abstract: Salgado-Somoza A, Teijeira-Fernández E, Fernández AL, González-Juanatey JR, Eiras S. Proteomic analysis of epicardial and subcutaneous adipose tissue reveals differences in proteins involved in oxidative stress. Am J Physiol Heart Circ Physiol 299: H202-H209, 2010. First published April 30, 2010; doi:10.1152/ajpheart.00120.2010.-Epicardial adipose tissue (EAT) is an endocrine organ adjacent to coronary arteries and myocardium without anatomy barriers. Locally produced adipokines may reflect or affect to cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 34 publications
(33 reference statements)
5
75
0
9
Order By: Relevance
“…Enhanced ROS production is an important factor associated with some cardiovascular diseases (20) such as CAD. Furthermore, we have previously observed that EAT presents higher oxidative stress than SAT (21).…”
Section: Introductionmentioning
confidence: 91%
“…Enhanced ROS production is an important factor associated with some cardiovascular diseases (20) such as CAD. Furthermore, we have previously observed that EAT presents higher oxidative stress than SAT (21).…”
Section: Introductionmentioning
confidence: 91%
“…The increase of proteins involved in the oxidative stress in EAT compared to that in SAT in patients with coronary artery disease suggests an association with increased myocardial oxidative stress in this category of patients [35].…”
Section: Biochemical Characteristics Of Eatmentioning
confidence: 91%
“…2 In addition, higher oxidative stress levels, including reactive oxygen species production and higher levels of enzymes involved in regulating oxidative stress such as catalase and glutathione S-transferase P, have been reported in epicardial fat relative to subcutaneous fat in patients with CAD. 52 In addition to the studies looking at gene expression of the inflammatory and oxidative stress markers, proteomic and secretome analyses of epicardial fat obtained from CAD patients have also revealed that it is capable of secreting factors that can induce atherogenic changes in monocytes and endothelial cells, 53 as well as induce cardiomyocyte dysfunction. 54 Conditioned media derived from epicardial fat of guinea pigs was also reported to induce insulin resistance in rat cardiomyocytes.…”
Section: Mechanisms Underlying the Pathophysiological Association Betmentioning
confidence: 99%